2019
DOI: 10.1111/1462-2920.14820
|View full text |Cite
|
Sign up to set email alerts
|

Interaction and assembly processes of abundant and rare microbial communities during a diatom bloom process

Abstract: Diatom blooms can significantly influence the dynamics of microbial communities, yet little is known about the interaction and assembly mechanisms of abundant and rare taxa during bloom process. Here, using 16S rRNA gene amplicon sequencing, we investigated the co-occurrence patterns and assembly processes of abundant and rare microbial communities during an early spring diatom bloom in Xiangshan bay. Our results showed that α-diversity indices in the rare subcommunity (RS) were significantly higher than those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
26
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(36 citation statements)
references
References 59 publications
8
26
2
Order By: Relevance
“…5b). This suggests that abundant taxa occupied more central locations within the network (17), which nicely aligns with findings reported in other previous studies (6,20).…”
Section: Abundant Taxa Occupy Central Nodes In the Co-occurrence Networksupporting
confidence: 92%
See 1 more Smart Citation
“…5b). This suggests that abundant taxa occupied more central locations within the network (17), which nicely aligns with findings reported in other previous studies (6,20).…”
Section: Abundant Taxa Occupy Central Nodes In the Co-occurrence Networksupporting
confidence: 92%
“…Co-occurrence network analysis is a powerful tool to determine potential interaction among bacterial taxa (15,16). The different roles of abundant and rare taxa in the co-occurrence network were revealed in recent studies (6,(17)(18)(19)(20). For instance, Jiao et al (17) reported a more important role for abundant taxa than for rare taxa in the network of oil-contaminated soils.…”
mentioning
confidence: 99%
“…Rare OTUs were defined as the OTUs with relative abundance <0.1% in all samples analysed, whereas abundant OTUs were defined as the OTUs with a relative abundance >1% in one or more samples (Zhang et al ., ). The latter contained both OTUs that were abundant ubiquitously and occasionally across the transect (Shade et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…Determining the differences in the community assembly processes between RT and AT is critical to understand the responses of a rare biosphere to environmental changes. Recently, such differences in different ecosystems, including agricultural fields (11)(12)(13), subtropical bays (14,15), and Tibetan Plateau grassland (16), have been widely studied. These studies showed that AT and RT generally exhibit distinct distribution patterns and assembly processes.…”
mentioning
confidence: 99%